Development of tourism industry and its impact on Langkawi Island community - Norlida Hanim Mohd Salleh,; Redzuan Othman,; Siti Hajar Mohd Idris,; Sharina Abdul Halim,; MD Shafiin Shukor,; Ishak Yussof,; Mohd Samsudin,; Mustafa Omar, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Langkawi Island is one of the most popular tourist destinations in Malaysia among both domestic and international tourists. The development of the tourism industry on this island has brought direct and indirect impact to the local communities. The objective of the present study is to analyze the impact of tourism development on the local communilt of Langkawi. This study is based on the perspectives of 493 local residents selected using multistage cluster sampling. Questionnaires qre used as an instrument to collect data via a face to face interview in predetermined locations which are in proximity to tourist destination areas. Based on the social exchange theory $er), 24 variables are examined. Statistical techniques used to analyze data in this study include mean analysis, exploratory factor analysis (zr,l) and regression analysis. The results for the mean analysis show thatfive variables that have the highest mean score qre; increasing the provision of appropriate employment opportunities (4.15); encouraging tourists to come and spend their money in Langkawi (a.|a); increasing communityb pride in their own culture G 09); providing employment opportunity for the local residents (a.09); and attracting investors to Langkawi (4.07). Exploratory factor analysis (oru) is conducted resulting in all the 24 variables grouped into 4 constructs namely economic, social, cultural and environmental factors. However, only social, cultural and economic factors are statistically significant in influencing the overall perceptions on tourism development impact on the island based on a multiple regression analysis. Although environmental factor is not significant in the regression model, based on the mean analysis this sndy concludes that there is a slight environmental degradation due to tourism development on this island. The mean analysis also shows that in general, the community perceived that tourism development brings positive impact. Hence, local community b active participation in the industry is encouraged. Stakeholders in the tourism industry in Langkawi such as the federal and state governments; and private agencies, must engage in more proactive initiatives to ensure continuous participation from the local community which consequently will result in a long run sustainable development of the tourism industry on the island.